Critical Review of Global Health Policies in Comparative Analysis of Developed and Developing Healthcare Systems and Innovations and Challenges in Service Access and Quality - Alderian, Fahad Mohammed Ahmed; Alkhuraym, Saleh Masoud Mahdi; Alnaseeb, Yahia Abudallh Hussain; Alyami, Mansour Ali Mohammad; Al khomsan, Hamad Salem Yahya; Almossaid, Moammar Abbas Ali; Alkomssan, Mohammad Salem Yahya; AlGareh, Yahya Magbool Yahya; Hashil, Ibrahim Saleh Mohammed; Aldhairiyan, Nabeel Mohsen (Journal of Ecohumanism, 2024)
This paper critiques current global health welfare policies concerning the comparative healthcare structure in developed and developing countries. However, as seen in the following analysis of the healthcare frameworks, innovations, and challenges faced by both sets of countries, the study affords a more nuanced understanding of global healthcare. The two cases raise fundamental issues regarding disparity within a health system regarding service provision, quality of care, and the use of technology in the contemporary practice of health care. It looks at the possibilities and challenges in healthcare settings but with a particular focus on the strategies that could be used to support the eradication of inequities in world health. Policy implications for enhancing service availability and quality are then discussed in the paper’s final part for the developed and developing regions.